Schisandra chinensis and Morus alba Synergistically Inhibit In Vivo Thrombus Formation and Platelet Aggregation by Impairing the Glycoprotein VI Pathway - Kim, Dong-Seon (Evid Based Complement Alternat Med, 2017)
Morus alba L. (MAL) extract has been used in traditional medicine for its cardioprotective and antiplatelet effects, while another herbal remedy, Schisandra chinensis (SCC), has been reported to have anti-inflammatory and antioxidant properties. We evaluated underlying cellular changes exerted by extracts of these plants on platelet function and effects of SCC + MAL on in vivo thrombus formation using AV shunt and tail thrombosis-length models in rats. In vitro platelet aggregation, granule secretion, and [Ca(2+)](i) release assays were carried out. The activation of integrin α(IIb)β(3) and phosphorylation of downstream signaling molecules, including MAPK and Akt, were investigated using cytometry and immunoblotting, respectively. Scanning electron microscopy (SEM) was used to evaluate changes in platelet shape and HPLC analysis was carried out to identify the marker compounds in SCC + MAL mixture. In vivo thrombus weight and average length of tail thrombosis were significantly decreased by SCC + MAL. In vitro platelet aggregation, granule secretion, [Ca(2+)](i) release, and integrin α(IIb)β(3) activation were notably inhibited. SCC + MAL markedly reduced the phosphorylation of MAPK pathway factors along with Akt. HPLC analysis identified four marker compounds: isoquercitrin, astragalin, schizandrol A, and gomisin A. The extracts exerted remarkable synergistic effects as natural antithrombotic and antiplatelet agent and a potent drug candidate for treating cardiovascular diseases.